AYURVEDIC REVIEW OF DIABETES MELLITUS (PRAMEHA) - Karnawat, Tushar Ravindra; Yavatkar, P. C. (International Journal of Research -GRANTHAALAYAH, 2017)
India is set to emerge as the diabetic capital of the world and it is very shameful prediction which India has to face. Heredity, Sedentary life style, lack of exercise and yoga, stress, and improper diet habits are main reasons for spreading of the diabetes. In order to prevent the primary onset we need to concentrate on the next generation of existing diabetes patients. Making them aware will be the first task, followed by provocation for action, followed by action in reality. As diabetes is metabolic disorder it cannot be treated merely by controlling blood sugar level. Ayurveda aimed at rejuvenating the body for not only controlling blood sugar level but also ensure that no further complication should be caused. Ayurvedic treatment for diabetes based on entire change in life style of the person, along with proper medication and diet patient is advised to lead healthy and active life.